2014
DOI: 10.1371/journal.pone.0085192
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Individual Finger Movements from One Hand Using Human EEG Signals

Abstract: Brain computer interface (BCI) is an assistive technology, which decodes neurophysiological signals generated by the human brain and translates them into control signals to control external devices, e.g., wheelchairs. One problem challenging noninvasive BCI technologies is the limited control dimensions from decoding movements of, mainly, large body parts, e.g., upper and lower limbs. It has been reported that complicated dexterous functions, i.e., finger movements, can be decoded in electrocorticography (ECoG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 79 publications
3
126
1
2
Order By: Relevance
“…Recently, it was demonstrated that MRCPs associated with movements performed with different levels of force and speed of the same body part (wrist and foot movements) could be decoded from the EEG using only information prior to the onset of the movement [13,14,21]. Also, different movement types have been classified such as hand grasping, opening and reaching [1,2,4], movement direction and kinematics (see [19] for a recent review), wrist movements [12,[40][41][42], shoulder and elbow movements [8,[47][48][49] and finger movements [26,27,44].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that MRCPs associated with movements performed with different levels of force and speed of the same body part (wrist and foot movements) could be decoded from the EEG using only information prior to the onset of the movement [13,14,21]. Also, different movement types have been classified such as hand grasping, opening and reaching [1,2,4], movement direction and kinematics (see [19] for a recent review), wrist movements [12,[40][41][42], shoulder and elbow movements [8,[47][48][49] and finger movements [26,27,44].…”
Section: Introductionmentioning
confidence: 99%
“…We applied FBCSP as feature extraction method because it uses frequency filtering into multiple frequency bands, which could benefit the decoding of different motor tasks as demonstrated previously [33]. Furthermore, CSP algorithm has been proven its efficacy calculating optimal spatial filters for motor related BCIs [25,33,35]. Spatial filters were created for three frequency windows: 7-15 Hz, 15-25 Hz, and 25-30 Hz.…”
Section: (B))mentioning
confidence: 99%
“…Liao et al investigated the binary classification of ten different pairs of executed finger movements using 128-channel EEG signals achieving a promising average decoding performance of 77.1% [35]. In another study, six different wrist movement pairs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They tried to implement similar techniques but using EEG. Since earlier studies found that low-pass filtered ECoG (local motor potential LMP) shows precise features, Liao et al [4] tried to decode individual finger movement, hence they used findings from previous ECoG and implemented them using EEG, hence compared the results with ECoG findings. More complex techniques try to estimate the movement and approach of the hands.…”
Section: B Decoding and Orthosis Controlmentioning
confidence: 99%